The Role of International Collaboration in Enhancing Lecturers Research and Community Service - Edward Alezandro Lbn. Raja; Togu Harlen Lbn. Raja; Dato Zainal Abidin Bin Sakom; Eva Rianty Sitanggang; Riomas Sinurat; Adiwima Zebua (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This overseas lecturer community service program aimed to strengthen knowledge exchange through cooperation between Yayasan Lembaga Manajemen Indonesia/Institut Bisnis dan Komputer Indonesia and Yayasan Basmi Kemiskinan Selangor Malaysia. It was conducted on 30 July 2026 in Petaling Jaya, Selangor, Malaysia, through planning, preparation, implementation, and evaluation stages. The activity focused on the strategic role of international cooperation in improving lecturer research and community service, including strengthening research networks, exchanging academic experiences, improving lecturer competence, and supporting the implementation of the Tri Dharma of Higher Education. The material presentation was followed by discussion and oral evaluation to determine participants’ understanding of the topics delivered. The results showed that participants understood the material well and valued the exchange of knowledge and institutional experience. Continued cooperation between both institutions is expected to strengthen lecturer competence, expand international academic collaboration, and improve the implementation of research and community service activities.